2014
DOI: 10.1111/pace.12470
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Atrial Fibrillation in Patients with High CHADS2‐ and CHA2DS2VASc‐Scores: Anticoagulate or Monitor High‐Risk Patients?

Abstract: BackgroundIn patients with known atrial fibrillation (AF) different scores are utilized to estimate the risk of thromboembolic events and guide oral anticoagulation. Diagnosis of AF strongly depends on the duration of electrocardiogram monitoring. The aim of this study was to use established scores to predict the prevalence of AF.MethodsThe CHADS2- (Congestive Heart failure, hypertension, Age >75 years, Diabetes, Stroke [doubled]) and CHA2DS2VASc-score (Congestive Heart failure, hypertension, Age ≥75 years [do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 27 publications
1
15
0
Order By: Relevance
“…In a study by Mitchell and colleagues 17 ) , the CHADS 2 and CHA 2 DS 2 -VASc scores were predictive for subsequent hospital discharge with a diagnosis of AF in acute coronary syndrome. In 2013, Chao and colleagues 39 ) also reported that the incidence of AF progressively increased when patients had more complicated systemic diseases, as indicated by a high CHADS 2 score; this is in agreement with the finding of Tischer and colleagues that the prevalence of AF increases with increasing CHADS 2 and CHA 2 DS 2 -VASc scores 40 ) . These studies support the finding that higher CHADS 2 and CHA 2 DS 2 -VASc scores can identify patients who are more likely to develop asymptomatic AF.…”
Section: Discussionsupporting
confidence: 69%
“…In a study by Mitchell and colleagues 17 ) , the CHADS 2 and CHA 2 DS 2 -VASc scores were predictive for subsequent hospital discharge with a diagnosis of AF in acute coronary syndrome. In 2013, Chao and colleagues 39 ) also reported that the incidence of AF progressively increased when patients had more complicated systemic diseases, as indicated by a high CHADS 2 score; this is in agreement with the finding of Tischer and colleagues that the prevalence of AF increases with increasing CHADS 2 and CHA 2 DS 2 -VASc scores 40 ) . These studies support the finding that higher CHADS 2 and CHA 2 DS 2 -VASc scores can identify patients who are more likely to develop asymptomatic AF.…”
Section: Discussionsupporting
confidence: 69%
“…Since we referred in our model to the 2016 ESC Guidelines for the management of atrial fibrillation, we did not take into account cost-effectiveness measurement in a model which is based on a possible future concept of OAC therapy in patients without documented AF but with elevated stroke risk. So a study by Tischer et al found that, in patients with high CHA2DS2VASc-scores, thromboembolic complications occurred irrespective of the presence of AF and concluded that anticoagulant therapy may be initiated irrespective of documented AF [ 38 ]. But superiority of this new concept for prevention of stroke has not been proven so far.…”
Section: Discussionmentioning
confidence: 99%
“…While CHADS 2 /CHA 2 DS 2 -VASc score has been found to increase the risk of AF [ 41 ], this parameter has not been recognized as a significant risk factor in the post-CS setting [ 24 , 40 ]. This may be due to sample size issues or the high prevalence of elevated CHADS 2 /CHA 2 DS 2 -VASc score in this secondary prevention population.…”
Section: Identifying Patients At Risk Of Af After Cs or Tiamentioning
confidence: 99%